Cell-instructive starPEG-heparin-collagen composite matrices. (15th April 2017) - Binner, Marcus; Bray, Laura J.; Friedrichs, Jens; Freudenberg, Uwe; Tsurkan, Mikhail V.; Werner, Carsten
Graphical abstract: Abstract: Polymer hydrogels can be readily modulated with regard to their physical properties and functionalized to recapitulate molecular cues of the extracellular matrix (ECM). However, they remain structurally different from the hierarchical supramolecular assemblies of natural ECM. Accordingly, we herein report a set of hydrogel composite materials made from starPEG-peptide conjugates, maleimide-functionalized heparin and collagen type I that combine semisynthetic and ECM-derived components. Collagen fibrillogenesis was controlled by temperature and collagen concentration to form collagen microstructures which were then homogeneously distributed within the 3D composite matrix during hydrogel formation. The collagen-laden hydrogel materials showed a heterogeneous local variation of the stiffness and adhesion ligand density. Composite gels functionalized with growth factors and cell adhesive peptides (RGDSP) supported the growth of embedded human umbilical cord vein endothelial cells (HUVECs) and induced the alignment of embedded bone marrow–derived human mesenchymal stem cells (MSCs) to the collagen microstructures in vitro . The introduced composite hydrogel material is concluded to faithfully mimic cell-instructive features of the ECM. Statement of Significance: Cell-instructive materials play an important role in the generation of both regenerative therapies and advanced tissue and disease models. For that purpose, biofunctional polymer hydrogels recapitulating molecular cues of the extracellular matrix (ECM) were successfully applied in various different studies. However, hydrogels generally lack the hierarchical supramolecular structure of natural ECM. We have therefore developed a hydrogel composite material made from starPEG-peptide conjugates, maleimide-functionalized heparin and collagen type I fibrils. The collagen-laden scaffolds showed a heterogeneous local variation in the stiffness of the material. The composite gels were successfully tested in culture experiments with human umbilical cord vein endothelial cells and bone marrow–derived human mesenchymal stem cells. It was concluded that the composite scaffold was able to faithfully mimic important cell-instructive features of the ECM.